The maintenance of elevated active chlorine levels in the Antarctic lower straosphere through HCl null cycles - Müller, Rolf; Grooss, Jens-Uwe; Zafar, Abdul Mannan; Lehmann (EGU, 2017)
The Antarctic ozone hole arises from ozone destruction driven by elevated levels of ozone destroying ("active") chlorine in Antarctic spring. These elevated levels of active chlorine have to be formed first and then maintained throughout the period of ozone destruction. It is a matter of debate, how this maintenance of active chlorine is brought about in Antarctic spring, when the rate of formation of HCl (considered to be the main chlorine deactivation mechanism in Antarctica) is extremely high. Here we show that in the heart of the ozone hole (16–18 km or 100–70 hPa, in the core of the vortex), high levels of active chlorine are maintained by effective chemical cycles (referred to as HCl null-cycles hereafter). In these cycles, the formation of HCl is balanced by immediate reactivation, i.e. by immediate reformation of active chlorine. Under these conditions, polar stratospheric clouds sequester HNO3 and thereby cause NO2 concentrations to be low. These HCl null-cycles allow active chlorine levels to be maintained in the Antarctic lower stratosphere and thus rapid ozone destruction to occur. For the observed almost complete activation of stratospheric chlorine in the lower stratosphere, the heterogeneous reaction HCl + HOCl, the production of HOCl via HO2 + ClO, with the HO2 resulting from CH2O photolysis, is essential. These results are important for assessing the impact of changes of the future stratospheric composition on the recovery of the ozone hole. Our simulations indicate that, in the lower stratosphere, future increased methane concentrations will not lead to enhanced chlorine deactivation (through the reaction CH4 + Cl → HCl + CH3) and that extreme ozone destruction to levels below ≈ 0.1 ppm will occur until mid-century.